Varieties of agencies during working life changes - Anu Järvensivu (European Journal for Research on the Education and Learning of Adults, 2020)
The aim of this study is to shed light on the varieties of workers´ agencies in working life change situations, which is an under-researched topic in the literature of workplace learning and in working life studies. The research questions are what kinds of agencies there are to be found when workers encounter changes and how the different kinds of agencies are connected together. The understanding of agency is grounded on the subject-centered socio-cultural approach, whereas the methodological approach is based on applying life-course perspective on research material consisting of 48 working life narratives written by Finnish adults. The narratives are analyzed by abductive content analysis. The results reveal the dynamical and periodical processes between the different kinds of agencies during one´s working life narrative. The different forms of agency overlap and rotate. Suffering can be seen as a dynamic concept mediating transformative agencies, small agency and resistance.